The governance of the International Monetary Fund - Buira, A (University of Oxford, 2001)
Since 1997, following the approval of the Guidance Note on Governance by the Executive Board, the IMF has given increased attention to governance issues in its member countries. In view of its influence, it is of interest to consider to what extent the Fund's own governance meets the standards of transparency and accountability required for the good use of public resources. The paper reviews the power structure of the Fund, i.e. the distribution of quotas and the role of the Executive Board and of the staff and management in decision making. It finds that the concentration of power in a few countries impairs the transparency and political accountability of the Fund. It argues that as the changes in the world economy since the Bretton Woods Conference in 1944 have not been appropriately reflected in the quota structure some aspects of the system have become dysfunctional.